3D printing in tissue engineering: a state of the art review of technologies and biomaterials. Issue 7 (17th June 2020) - Poomathi, Nataraj; Singh, Sunpreet; Prakash, Chander; Subramanian, Arjun; Sahay, Rahul; Cinappan, Amutha; Ramakrishna, Seeram
Abstract : Purpose: In the past decade, three-dimensional (3D) printing has gained attention in areas such as medicine, engineering, manufacturing art and most recently in education. In biomedical, the development of a wide range of biomaterials has catalysed the considerable role of 3D printing (3DP), where it functions as synthetic frameworks in the form of scaffolds, constructs or matrices. The purpose of this paper is to present the state-of-the-art literature coverage of 3DP applications in tissue engineering (such as customized scaffoldings and organs, and regenerative medicine). Design/methodology/approach: This review focusses on various 3DP techniques and biomaterials for tissue engineering (TE) applications. The literature reviewed in the manuscript has been collected from various journal search engines including Google Scholar, Research Gate, Academia, PubMed, Scopus, EMBASE, Cochrane Library and Web of Science. The keywords that have been selected for the searches were 3 D printing, tissue engineering, scaffoldings, organs, regenerative medicine, biomaterials, standards, applications and future directions. Further, the sub-classifications of the keyword, wherever possible, have been used as sectioned/sub-sectioned in the manuscript. Findings: 3DP techniques have many applications in biomedical and TE (B-TE), as covered in the literature. Customized structures for B-TE applications are easy and cost-effective to manufacture through 3DP, whereas on many occasions, conventional technologies generally become incompatible. For this, this new class of manufacturing must be explored to further capabilities for many potential applications. Originality/value: This review paper presents a comprehensive study of the various types of 3DP technologies in the light of their possible B-TE application as well as provides a future roadmap.